1999
DOI: 10.30539/ijvm.v23i1.1191
|View full text |Cite
|
Sign up to set email alerts
|

Study on the pathology and parasitic affection of liver in sheep and cattle at Mosul area

Abstract: A sample of (700) seven hundred out of (3000) three thousand randomly collected livers of sheep and cattle from Mosul abattoir during a biweekly visits of six months period , has been subjected to both grads and histopathological examinations.  Results indicated that parasites induced the highest percen tages of tissue changes in the livers of cattle and sheep, the parasites responsible were Hydatid Cysts and Fasciola gigantica which indicated that Mosul and surrounding areas were endemic with these para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…It was found that most hydatid cycts were observed in lungs (17.16%) versus the liver (14.42%) which resembled to the explanation of occurrence stressed by [16]who stated that about 70% of hydatid cysts exist in the lungs and 25% were present in the livers. The prevalence of hydid cysts were slightly higher than those noted earlier by several local investigators in Mosul abattoir which were 9.3% [17]; 7.3% [18] and 5.5% [19] but in accorodnce with 15.5% recorded by [20] of Duhok slaughter house. It was noticed that 15.1% of the affected livers has single and diffuse abscesses which is much lower than those reported in Jordan sheep [9] and Iraqi sheep [21].…”
Section: Discussioncontrasting
confidence: 54%
“…It was found that most hydatid cycts were observed in lungs (17.16%) versus the liver (14.42%) which resembled to the explanation of occurrence stressed by [16]who stated that about 70% of hydatid cysts exist in the lungs and 25% were present in the livers. The prevalence of hydid cysts were slightly higher than those noted earlier by several local investigators in Mosul abattoir which were 9.3% [17]; 7.3% [18] and 5.5% [19] but in accorodnce with 15.5% recorded by [20] of Duhok slaughter house. It was noticed that 15.1% of the affected livers has single and diffuse abscesses which is much lower than those reported in Jordan sheep [9] and Iraqi sheep [21].…”
Section: Discussioncontrasting
confidence: 54%
“…There were significant decreased in RBC counts, Hb concentration and PCV percentage in the diseased sheep compared with control group which confirmed anemia in the infected sheep ,These result was in agreement with other reports (6,22,23) Bell-Sakyi et al (24) showed the significant lower of PCV of sheep carrying Anplasma and or/Theileria than of sheep without parasite. In addition, Al-Sultan et al (25) and Karawan (26) reported that decreased in RBC counts, Hb concentration and PCV percentage in Theileria-infected cattle. The pathogenesis of the anemia is not clear but occurs reasons hemolytic factor reported in the serum of acute affected cattle and may macrophages can damage red blood cells (2).…”
Section: Resultsmentioning
confidence: 98%
“…[1], [2]. A multitude of hepatic disorders remain undetected as a result of symptoms that are ambiguous or lack specificity [3]. The effectiveness of hematology and serum biochemistry has been called into question by [4], [5], necessitating the use of additional auxiliary tests as suggested by [6].…”
Section: Introductionmentioning
confidence: 99%